The Implementation of H5P in Interactive Games for Cyber Security Awareness Learning Facilities for Elementary and Junior High School Students - Mazura Binti Mat Din; Shaifizat Mansor; Siti Rafidah Muhamat Dawam; Andria Andria; Ridam Dwi Laksono; Kelik Sussolaikah (Universitas Ahmad Dahlan, 2023)
The importance of digital security awareness is not only related to privacy protection but also includes responsible use, protection from cyberbullying, and understanding the consequences of online actions. In primary and secondary schools, understanding regarding cyber security awareness is still lacking; students must realize that what they do in the digital world can have long-term impacts on their real lives. An introduction and understanding of digital security awareness need to be given to elementary and junior high school students. This study intended to provide a vehicle (learning tool) and introduce cyber security awareness using interactive games. By using the Moodle platform and the H5P plugin to make games more interactive, interesting, effective, and efficient. This activity was carried out using the RnD method. With the RnD method, the development of awareness and the many ways to protect oneself on the internet can be developed significantly, according to the level of understanding of students Game platform development uses a Moodle-based learning management system. Then do the customization using H5P. Meanwhile, games are developed by taking into account cyber security awareness indicators. Game applications that are compiled can run well. The trial was conducted on 4 elementary schools and 4 junior high schools. During the trial, the platform's reliability can run smoothly when accessed by users. There were no obstacles in using games by the user during the trial. User features related to achievement badges, as an indication of the level of play each player can achieve responsively. Interactive games about cyber security awareness can be formed and run according to the design set. The contribution of this research is to increase students' understanding of internet safety awareness through interactive games and to increase students' knowledge about how to protect themselves while surfing the internet through interactive games.